(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Approximately 70 million patients undergo surgical procedures each year, with 75 to 80% experiencing moderate to severe postoperative pain. This situation is concerning, as poorly controlled postoperative pain can lead to additional complications, prolonged recovery time, and diminished patient quality of life. Method The present study aims to validate the psychometric relevance of the Brief Pain Inventory (BPI) by confirming its two primary dimensions: pain intensity and its interference with activities and psychosocial well-being. The findings reveal that while pain management effectively preserves psychological and social dimensions, such as sleep and interpersonal relationships, a significant proportion of patients (51%) continue to suffer from moderate to severe pain. This pain markedly impacts mobility and daily activities, with nearly 60% of patients perceiving pain management as insufficient. Additionally, 58% of patients report atypical pain, indicating the need for more targeted therapeutic adjustments. The data also reveal that 42% of patients report mild pain or impact according to the global BPI score. However, 38% of patients experience moderate pain or impact, signaling partial interference with daily activities. Finally, 20% of patients suffer from severe pain or impact, highlighting the urgency for multimodal strategies combining pharmacological treatments, physical interventions, and psychological support to optimize postoperative quality of life. Conclusion These findings affirm the BPI as a valuable tool for evaluating and adapting pain management approaches across diverse clinical contexts. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 465-477